Nature-inspired nano-additives for Biofuel application – A Review - Vignesh, P.; Jayaseelan, Veerasundram; Pugazhendiran, P.; Prakash, M. Sathya; Sudhakar, Kumarasamy (Elsevier B.V., 2022)
The increasing demand and cost of conventional fuels have forced humanity to consider various alternative fuels. Low yield and massive cost are significant limitations in biofuel production. Nanotechnology has emerged as a prominent research area in the scientific community with a wide range of applications, including biofuels. This review discusses the specific approaches and methods to synthesize nanoparticles from natural materials. In addition, it summarizes the use of nanocatalyst, nano-additives and microbial enzymes to enhance biofuel properties and production processes. This review also highlights the effect of plant-based nanoparticles on diesel engines' combustion performance and emissions.